Genomic characterization reveals potential biomarkers in nasopharyngeal carcinoma patients with relapse. (1st November 2020) - Cho, William C. S.; Tse, Ka-Po; Ngan, Roger K. C.; Cheuk, Wah; Ma, Victor W. S.; Yang, Yi-Ting; Yip, Timothy T. C.; Tan, Kien Thiam; Chen, Shu-Jen
ABSTRACT: Background: Although the majority of nasopharyngeal carcinoma (NPC) patients demonstrate favorable outcomes after radiotherapy and/or chemotherapy, about 8–10% of patients will develop recurrent disease, and genomic alterations (GAs) associated with the recurrence are unclear. Methods: This study investigated the GAs in the paired primary tumors and recurrent tumors of 7 NPC patients with relapse, as well as the primary tumors of 15 NPC patients without relapse by deep targeted next-generation sequencing on 440 cancer-related genes. Results: BRCA1 and TP53 mutations were significantly enriched in patients with relapse ( P = 0.021 and P = 0.023, respectively). Survival analysis revealed that the GAs of TP53, ZNF217, VEGFB, CDKN1B, GNAS, PRDM1, and MEN1 were associated with significantly shorter overall survival. The GAs of the tumor also altered after treatment in the relapsed group, and five genes ( CDK4, FGFR3, ALK, BRCA1, and CHEK2 ) in the recurrent tumors were potentially druggable. Conclusions: The discovery of GAs associated with recurrence or survival in NPC may serve as potential prognostic gene signatures of high-risk patients. Targeted therapies are available in some of the clinically relevant GAs and may be considered in future clinical trials. Given the limitation of the sample size, validation by a larger cohort is warranted.